Shtrikhi k portretu . Shtrikhi k portretu . Touches to the Portrait . Штрихи к портрету - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Segment on a singer and honored artist of the republic of Sakha (IAkutiia) Alexandr Alexeev; amateurs' performance competition in Kursk; gardening in Kislovodsk; exhibition by the artist Israel TSvaygenbaum in Moscow; a small enterprise in Orenburg producing lacework; interview with the director of a furniture company. Contributors: Romankova, Svetlana (Anchor) О певце, заслуженном артисте республики Саха (Якутия) Александре Алексееве; о конкурсе самодеятельных коллективов в Курске; садоводство в Кисловодске; выставка художника Исраиля Цвайгенбаума в Москве; о малом предприятии в Оренбурге, производящем кружевные изделия; интервью с владельцем фирмы по продаже мебели. Создатели: Романкова, Светлана (Ведущий/Ведущая)